Strategi Pembelajaran Berbasis Cerita sebagai Inovasi Penguatan Karakter Siswa Kelas Rendah Sekolah Dasar - Syahputra, Ridwan; Wahyudi, Mateus Eka (Medan Resource Center, 2025)
Many lower-grade elementary school students in Indonesia exhibit behavioral issues such as indiscipline, irresponsibility, and lack of empathy, often attributed to language learning approaches that emphasize cognitive development while neglecting affective dimensions. This study aims to explore and analyze the implementation of story-based learning strategies as an innovative approach to reinforce character education among early-grade students. Employing a literature review method, the study draws upon scholarly books, peer-reviewed journals, and relevant academic reports as data sources. The data were examined through content analysis to uncover recurring themes, conceptual linkages, and significant pedagogical insights. The findings reveal that storytelling possesses strong potential for moral value internalization, aligning well with the cognitive and emotional development stages of young learners. The study concludes that story-based learning is an effective, integrative strategy for embedding character education within Indonesian language instruction, offering a holistic approach to shaping positive student behavior.